Pauline Christianity : Luke-Acts and the legacy of Paul - Mount, Christopher N., 1962- (Novum Testamentum, Supplements, 2002)
Pauline Christianity takes a fresh perspective on the composition and reception of Luke-Acts in relation to the category 'Pauline Christianity' as it has been used to describe traditions, communities, and persons connected to Paul. This inquiry is pursued along three lines. (1) The reception of the Acts of the Apostles and the 'Pauline' Luke by Irenaeus is addressed. (2) The compositional intentions of the author of Luke-Acts in constructing 'Pauline' Christianity are analyzed. (3) The literary Paulinism of the author is separated from the Paulinism of his sources. This study contributes to the ongoing discussion of Paul's role in the history of early Christianity by making clear the extent to which the 'Pauline Christianity' of Luke-Acts has its origins in various second-century attempts to reconstruct the Christian origins.